Meningkatkan Hasil Belajar Materi Ciri-Ciri Makhluk Hidup Dengan Model Problem Posing Pada Siswa Kelas III SDN 1 Selopuro - Pujiarti, Pujiarti (Universitas Sebelas Maret, 2020)
The purpose of this study is to describe the improvement of learning outcomes and completeness of learning to present reports on the concept of the characteristics of living things after being given learning with the Problem Posing learning model to third grade students of SD Negeri 1 Selopuro, Batuwarno District, Wonogiri Regency, semester 1 of the 2019/2020 academic year. The research was conducted using a comparative method, namely comparing the results of observations and test results. Learning outcomes were indicated by the percentage of completeness in the pre-cycle 36.36%, in Cycle I the students completed to 54.55% and in the second cycle to 81.82%. This increase is shown that the Problem Posing Learning Model can improve learning outcomes in third grade students of SD Negeri 1 Selopuro, Batuwarno District, Wonogiri Regency in semester 1 of the 2019/2020 academic year.